Clinical Characteristics, Prenatal Diagnosis and Outcomes of Placenta Accreta Spectrum in Different Placental Locations: A Retrospective Cohort Study - Feng X; Mao X; Zhao J (Dove Medical Press, 2024)
Xiaoling Feng,1 Xun Mao,1 Jianlin Zhao2,3 1Department of Obstetrics and Gynecology, The Third Affiliated Hospital of Chongqing Medical University, Chongqing, 401120, People's Republic of China; 2The Department of Obstetrics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People's Republic of China; 3Chongqing Key Laboratory of Maternal and Fetal Medicine, Chongqing Medical University, Chongqing, 400016, People's Republic of ChinaCorrespondence: Jianlin Zhao; Xun Mao, Email zjlchongqing@gmail.com; maoxun@hospital.cqmu.edu.cnObjective: To explore the prenatal diagnosis, clinical characteristics, and perinatal outcomes of placenta accreta spectrum in different placental locations.Methods: This was a retrospective cohort study. Pregnant women who delivered at two tertiary referral hospitals from January 2013 to December 2022 and were ultimately pathologically diagnosed with placenta accreta spectrum were included. They were divided into three groups based on different placental locations (anterior, posterior, and lateral wall/fundus). The differences in prenatal diagnosis, clinical characteristics, and perinatal outcomes among the three groups were compared.Results: There were 115,470 deliveries in a ten-year period at the two hospitals, and 118 case patients were confirmed to have a pathologically diagnosed placenta accreta spectrum. The posterior placenta group had a lower rate of placenta previa (76.9% vs 94.9% vs 100%, p< 0.05) and a higher gestational age at delivery (36.4± 2.45 vs 34.91± 1.76 vs 34.31± 3.41, p< 0.05) compared to the other two groups. The anterior placenta group had a significantly higher rate of invasive (increta/percreta) form placenta accreta spectrum (81.4% vs 36.5% vs 28.6%, p< 0.05) and planned cesarean section (96.6% vs 80.8% vs 71.4%, p< 0.05) compared to the other two groups. In terms of prenatal diagnosis, the anterior placenta group had a significantly higher rate of placenta accreta spectrum prenatal suspicion rate compared to the other two groups (86.4% vs 36.5% vs 57.1%, p< 0.05). The posterior placenta group had a lower rate of preoperative abdominal aortic balloon placement compared to the other two groups (5.8% vs 28.8% vs 28.6%, p< 0.05). There were no statistically significant differences among the three groups in primary perinatal outcomes, though the anterior placenta group had a longer postoperative hospital stay.Conclusion: The prenatal diagnosis rate and proportion of invasive form of placenta accreta spectrum occurring in non-anterior placenta are relatively lower than anterior placenta. There were no significant differences in major perinatal outcomes among the three groups.Keywords: placenta accreta spectrum, placenta location, clinical characteristics, perinatal outcomes